2004
DOI: 10.1111/j.1468-2982.2004.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Sumatriptan and Zolmitriptan Treatment on 5-HT1 Receptor Expression and Function in Rats

Abstract: Triptans are commonly used anti-migraine drugs and show agonist action mainly at serotonin 5-HT(1B/1D/1F) receptors. It is not known whether frequent or long-term treatment with these drugs would alter 5-HT receptor function. We investigated the effects of protracted (14-18 days) sumatriptan and zolmitriptan treatment in rats on 5-HT(1) receptor mRNA expression and function in tissues related to migraine pathophysiology. RT-PCR analysis revealed that 5-HT(1B/1D/1F) receptor mRNA was reduced in the trigeminal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 31 publications
1
34
0
1
Order By: Relevance
“…Our results with zolmitriptan in experimental animals are in accordance with pharmacological studies in humans where no significant changes in MAP have been described [23]. Also, previous studies indicate that sustained zolmitriptan administration does not cause tachyphylaxis [24][25]. In agreement with these data we observed 14% reduction of PVP in CBDL rats treated with zolmitriptan for one week.…”
Section: Discussionsupporting
confidence: 92%
“…Our results with zolmitriptan in experimental animals are in accordance with pharmacological studies in humans where no significant changes in MAP have been described [23]. Also, previous studies indicate that sustained zolmitriptan administration does not cause tachyphylaxis [24][25]. In agreement with these data we observed 14% reduction of PVP in CBDL rats treated with zolmitriptan for one week.…”
Section: Discussionsupporting
confidence: 92%
“…Chronically applied, the drugs induced a significant increase of 5HT synthesis in many projection areas but not in the dorsal raphe nucleus [14]. Reuter et al [16] demonstrated that chronic sumatriptan and zolmitriptan treatment (2 weeks) significantly reduces 5HT 1B/1D/1F mRNA in trigeminal ganglion cells. Thus, excessive use of anti-migraine medication may result in alterations of serotonergic neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic use of analgesic drugs could result in a decrease in the level of 5-HT and up-regulate the5-HT2A receptors in platelets (Srikiatkhachorn and Anthony, 1996;Srikiatkhachorn et al, 1998). Down-regulation of the 5-HT1 receptor (5-HT1B/1D) has also been demonstrated in animals receiving chronic treatment with an anti-migraine drug (Reuter et al, 2004). As mentioned above, 5-HT is a crucial pain modulator in trigeminal nociception; it plays an important role in controlling CGRP synthesis and release in TG.…”
Section: Discussionmentioning
confidence: 96%